Bilderbuch-Heimkehr? Remigration im Kontext - Straub, Wolfgang (Arco, 2017)
This publication addresses the topic of remigration - focussing on the return of exiles to Germany and Austria after 1945. The articles of this book explore the multidiscipli-nary field primarily from the point of view of social sciences and humanities, thereby aiming at a systematic approach.